The Interplay of Semantics, Pragmatics, and Digital Identity in Social Media Discourse: An Analysis of #JulidFisabilillah - Rambe, Agung Olaf Ridho; Mulyadi, Mulyadi (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
This study investigates the intricate relationship between semantics and pragmatics within the realm of virtual communication, with a particular emphasis on social media interactions. It explores how the meanings of words and phrases (semantics), in conjunction with the contextual factors surrounding their use (pragmatics), play a crucial role in shaping digital identity and fostering online community formation. The research reveals that language on social media functions not merely as a medium of information exchange but also as a vehicle for conveying emotions, attitudes, and opinions. Specific lexical choices and symbolic elements are shown to signify group affiliation and ideological positioning. The case study of the hashtag #JulidFisabilillah on Twitter exemplifies these phenomena, illustrating how hashtags can serve both as markers of collective identity and as reflections of broader socio,cultural discourses. Ultimately, the findings underscore that effective analysis of social media communication must extend beyond literal content to include consideration of contextual factors. This research contributes to a deeper understanding of digital discourse by foregrounding the interplay of semantics, pragmatics, and context in the construction of meaning and identity in online spaces